Analisis Faktor Risiko Low back Pain (LBP) Selama Pembelajaran Jarak Jauh (PJJ) pada Mahasiswa UPN Veteran Jakarta Tahun 2020 - Anisa Vidyakova Auliya Prameswita (2021)
COVID-19 has spread to almost all corners of the world. COVID-19 is expected to increase low back pain due to a change in the learning system from offline to online. The purpose of this study was to analyze the risk factors for low back pain (LBP) during distance learning (PJJ) among UPN Veteran Jakarta students in 2020. This type of research was quantitative analytic with a cross-sectional design. The sampling technique used purposive sampling with the number of samples of this study were 425 active students of UPN Veteran Jakarta. Data obtained by distributing questionnaires online and data analysis used is Chi-Square. The results showed that 318 respondents (74.8%) had complaints of low back pain. The results of statistical analysis showed an increased risk of LBP in women (POR = 1.80, 95% CI: 1.09-2.96) compared to men, with mild stress (POR = 2.83, 95% CI: 1.58 -5.09), moderate stress (POR = 2.63, 95% CI: 1.46-4.93), severe stress (POR = 2.93, 95% CI: 1.47-5.82) compared normal stress category, and the learning position is not ergonomic (POR = 3.01, 95% CI: 1.90-4.76) than the ergonomic learning position. There was no significant relationship between age, BMI, smoking behavior, moderate physical activity, low levels of physical activity and duration of study. Therefore, education is needed about LBP risk factors and how to prevent them.